Histone deacetylase inhibitors inhibit cervical cancer growth through Parkin acetylation-mediated mitophagy - Xin Sun; Yuhan Shu; Guiqin Ye; Caixia Wu; Mengting Xu; Ruilan Gao; Dongsheng Huang; Jianbin Zhang (Elsevier, 2022)
Parkin, an E3 ubiquitin ligase, plays a role in maintaining mitochondrial homeostasis through targeting damaged mitochondria for mitophagy. Accumulating evidence suggests that the acetylation modification of the key mitophagy machinery influences mitophagy level, but the underlying mechanism is poorly understood. Here, our study demonstrated that inhibition of histone deacetylase (HDAC) by treatment of HDACis activates mitophagy through mediating Parkin acetylation, leading to inhibition of cervical cancer cell proliferation. Bioinformatics analysis shows that Parkin expression is inversely correlated with HDAC2 expression in human cervical cancer, indicating the low acetylation level of Parkin. Using mass spectrometry, Parkin is identified to interact with two upstream molecules, acetylase acetyl-CoA acetyltransferase 1 (ACAT1) and deacetylase HDAC2. Under treatment of suberoylanilide hydroxamic acid (SAHA), Parkin is acetylated at lysine residues 129, 220 and 349, located in different domains of Parkin protein. In in vitro experiments, combined mutation of Parkin largely attenuate the interaction of Parkin with PTEN induced putative kinase 1 (PINK1) and the function of Parkin in mitophagy induction and tumor suppression. In tumor xenografts, the expression of mutant Parkin impairs the tumor suppressive effect of Parkin and decreases the anticancer activity of SAHA. Our results reveal an acetylation-dependent regulatory mechanism governing Parkin in mitophagy and cervical carcinogenesis, which offers a new mitophagy modulation strategy for cancer therapy.